Ciprofloxacin Release Using Natural Rubber Latex Membranes as Carrier - Heitor Dias Murbach; Guilherme Jaques Ogawa; Felipe Azevedo Borges; Matheus Carlos Romeiro Miranda; Rute Lopes; Natan Roberto de Barros; Alexandre Vinicius Guedes Mazalli; Rosângela Gonçalves da Silva; José Luiz Ferreira Cinman; Bruno de Camargo Drago; Rondinelli Donizetti Herculano (International Journal of Biomaterials)
Natural rubber latex (NRL) from Hevea brasiliensis is easily manipulated, low cost, is of can stimulate natural angiogenesis and cellular adhesion, is a biocompatible, material and presents high mechanical resistance. Ciprofloxacin (CIP) is a synthetic antibiotic (fluoroquinolone) used in the treatment of infection at external fixation screws sites and remote infections, and this use is increasingly frequent in medical practice. The aim of this study was to develop a novel sustained delivery system for CIP based on NRL membranes and to study its delivery system behavior. CIP was found to be adsorbed on the NRL membrane, according to results of energy dispersive X-ray spectroscopy. Results show that the membrane can release CIP for up to 59.08% in 312 hours and the mechanism is due to super case II (non-Fickian). The kinetics of the drug release could be fitted with double exponential function X-ray diffraction and Fourier transform infrared (FTIR) spectroscopy shows some interaction by hydrogen bound, which influences its mechanical behavior.